Druggable targets and therapeutic development for COVID-19 - Xiaohua Duan; Lauretta A. Lacko; Shuibing Chen (Frontiers in Chemistry, 2022)
Coronavirus disease (COVID-19), which is caused by SARS-CoV-2, is the biggest challenge to the global public health and economy in recent years. Until now, only limited therapeutic regimens have been available for COVID-19 patients, sparking unprecedented efforts to study coronavirus biology. The genome of SARS-CoV-2 encodes 16 non-structural, four structural, and nine accessory proteins, which mediate the viral life cycle, including viral entry, RNA replication and transcription, virion assembly and release. These processes depend on the interactions between viral polypeptides and host proteins, both of which could be potential therapeutic targets for COVID-19. Here, we will discuss the potential medicinal value of essential proteins of SARS-CoV-2 and key host factors. We summarize the most updated therapeutic interventions for COVID-19 patients, including those approved clinically or in clinical trials.